1998
DOI: 10.1109/86.712230
|View full text |Cite
|
Sign up to set email alerts
|

Separability of EEG signals recorded during right and left motor imagery using adaptive autoregressive parameters

Abstract: Electroencephalogram (EEG) recordings during right and left motor imagery can be used to move a cursor to a target on a computer screen. Such an EEG-based braincomputer interface (BCI) can provide a new communication channel to replace an impaired motor function. It can be used by, e.g., patients with amyotrophic lateral sclerosis (ALS) to develop a simple binary response in order to reply to specific questions. Four subjects participated in a series of on-line sessions with an EEG-based cursor control. The EE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
250
0
5

Year Published

2003
2003
2024
2024

Publication Types

Select...
3
3
3

Relationship

0
9

Authors

Journals

citations
Cited by 480 publications
(260 citation statements)
references
References 23 publications
5
250
0
5
Order By: Relevance
“…A second example is described by Garrett et al [27] who compare linear and nonlinear classifiers for the discrimination of EEG recorded while subjects perform one of five mental tasks. Previous work showed that a useful representation of multichannel windowed EEG signals consists of the parameters of an AR model of the data [1], [20]. One linear and two nonlinear classifiers were applied to EEG data represented as AR models.…”
Section: A Fixed Nonlinear Transformationsmentioning
confidence: 99%
See 1 more Smart Citation
“…A second example is described by Garrett et al [27] who compare linear and nonlinear classifiers for the discrimination of EEG recorded while subjects perform one of five mental tasks. Previous work showed that a useful representation of multichannel windowed EEG signals consists of the parameters of an AR model of the data [1], [20]. One linear and two nonlinear classifiers were applied to EEG data represented as AR models.…”
Section: A Fixed Nonlinear Transformationsmentioning
confidence: 99%
“…1, it should be clear whether a given method was to be used in the feature extractor or the feature classifier. For instance, an autoregressive (AR) modeling method might be used in the process of extracting features from the electroencephalogram (EEG) signal (for example, see [20]). On the other hand, a nearest neighbor classifier method could be applied in the feature classification process (for example, see [15]).…”
Section: Introductionmentioning
confidence: 99%
“…AAR assume that the weights a i can vary over time. It seems that (AAR) parameters would give better results than (AR) parameters for motor imagery classification (Schlögl et al, 1997;Pfurtscheller et al, 1998), whereas they would give worse results for the classification of cognitive tasks such as mental computations, mental rotation of a geometric figure, etc. (Huan & Palaniappan, 2004a;Huan & Palaniappan, 2004b).…”
Section: Among the More Used Parametric Modelling In Bcis Are The Autmentioning
confidence: 99%
“…Succeeding parts of the BCI system are responsible for: measuring brain activity, preprocessing of the acquired signals, describing the signals by a few relevant features (feature extraction), selecting the most relevant features (feature selection), assigning a class to a set of selected features (classification), executing a command assigned to the chosen class and providing feedback to the user informing him about the mental state recognized by the BCI system. Although, all steps of the loop have to be carefully designed in order to build a successful BCI system, four of them play the major role: preprocessing [2][3][4], feature extraction [5][6], feature selection [7][8][9] and classification [10][11][12]. This paper deals with the first of these four main steps, it is with the preprocessing step.…”
Section: Introductionmentioning
confidence: 99%